PENGARUH KEMUDAHAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT SECARA ONLINE MELALUI TRAVELOKA - Vania Nurshafira Ernando; Faiz Albanna (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This research aims to find out how much the ease of use and brand image influence on the decision to purchase plane tickets online through Traveloka. This research was conducted online in April 2021 in Cilacap, Central Java. The research uses a descriptive quantitative approach. The Types of data utilized in this study are primary and secondary data. Data collection is done by online send around questionnaires. The sampling method used is a purposive sampling technique. The amount of samples in this study is 96 respondents. Data analysis used in this research are descriptive analysis, validity test, reliability test, double linear regression analysis, partial test, simultaneous test, classical assumption test, and determination coefficient test. Based on partial test results, ease of use shows the sig > a (0.969 > 0.05) value and the brand image shows the sig < a (0.000 < 0.05). Whereas the simultaneous result shows the sig < a (0.000 < 0.05) value. The result of the coefficient determination test shows that ease of use and brand image influences purchase decisions by 50.8% and the leftovers are influenced by the other factors which are not included in this research. The research shows that in partial, ease of use doesn’t affect significantly on purchasing decision and brand image influences significantly on purchasing decision. Simultaneously, ease of use and brand image influences significantly on purchasing decisions.